Taxation of Farming Enterprises in Poland and the European Union - a Comparative Analysis - Elżbieta Klamut (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
Every state has the right to constitute its own burdens on economic activity. After Polish accession to the European Union the part of tax burden is being customized to the requirements of a community. Farm tax which is applied in taxation of Polish agriculture is an anachronism. How far does taxation in Poland diverge from the solutions in other EU countries? Will introduction of income tax in Polish agriculture impoverish the state budget or the opposite? These are just a few issues contained in this study.